Genesis and Evolution: From Multi-Part Tv Film to Tv Series - Eleonora Rinatovna Ganieva (International Journal on Integrated Education, 2022)
The article is devoted to the study of the phenomenon of serialism and the origin of the serial genre. The article analyses the similarities and differences in the terminology adopted in foreign countries and in the CIS countries. In addition, attention is paid to the process of series evolution from its original forms to modern formats operating in the system of traditional and interactive television, the Internet, etc.